Opportunities of ultrasound diagnostics of lung injury in SARS-CoV-2 infection (COVID-19): a clinical case - G. V. Neklyudova; А. V. Chernyak; N. А. Tsareva; S. N. Аvdeev (Туберкулез и болезни лёгких)
The article describes a clinical case demonstrating the results of the lungs ultrasound examination in the COVID-19 patient during the acute period of the disease and early recovery period.